1998
DOI: 10.1093/humrep/13.6.1606
|View full text |Cite
|
Sign up to set email alerts
|

Timing of oocyte activation, pronucleus formation and cleavage in humans after intracytoplasmic sperm injection (ICSI) with testicular spermatozoa and after ICSI or in-vitro fertilization on sibling oocytes with ejaculated spermatozoa

Abstract: In the first study, we evaluated 101 oocytes [2, 4, 6, 8, 16, 18 and 20 h after intracytoplasmic sperm injection (ICSI)] that had been microinjected with testicular spermatozoa. Of the 70 normally fertilized oocytes (69%) 30 (43%) had two pronuclei by 6 h after ICSI. Fifty-one (73%) by 8 h, 69 (99%) by 16 h and four of them by 20 h cleaved to the 2-cell stage. In the second study, 95 cumulus-corona-oocyte complexes (CCOC) were divided into two groups. Forty-seven CCOC were inseminated by conventional in-vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(51 citation statements)
references
References 25 publications
4
42
2
3
Order By: Relevance
“…It appears that the kinetics of pronuclear formation and polar body extrusion of parthenogenetically activated 2-day-old oocytes but not 1-day-old oocytes described herein were consistent with those of fresh oocytes after ICSI fertilization [14,15]. They reported that 68% of oocytes fertilized by ICSI had two clearly distinguishable polar bodies by 4 h. The first pronucleus appeared 6 h after ICSI and 80% of the normally fertilized oocytes revealed two pronuclei at 8 h, although time-lapse video-recording demonstrated a somewhat earlier start of pronucleus formation [16].…”
Section: Discussionsupporting
confidence: 51%
“…It appears that the kinetics of pronuclear formation and polar body extrusion of parthenogenetically activated 2-day-old oocytes but not 1-day-old oocytes described herein were consistent with those of fresh oocytes after ICSI fertilization [14,15]. They reported that 68% of oocytes fertilized by ICSI had two clearly distinguishable polar bodies by 4 h. The first pronucleus appeared 6 h after ICSI and 80% of the normally fertilized oocytes revealed two pronuclei at 8 h, although time-lapse video-recording demonstrated a somewhat earlier start of pronucleus formation [16].…”
Section: Discussionsupporting
confidence: 51%
“…We found that the incidence of D5 blastocysts with normal chromosomal constitution was higher than D6 blastocysts for bi-pronuclear zygotes. Previous studies indicated that the majority of normally fertilized zygotes were bi-pronuclear at 16-18 h post-insemination [Nagy et al 1998;Rienzi et al 2005], and embryos developed to the hatching blastocysts stage on D5 [Kirkegaard et al 2013]. When the pronuclear zygotes were reanalyzed 4-6 h later, however, 25% of the mono-pronuclear zygotes at 16-18 h post-insemination were found to have developed a second pronucleus [Staessen and Van Steirteghem 1997].…”
Section: Discussionmentioning
confidence: 97%
“…They also found that embryos derived after ICSI cleaved earlier compared to those after IVF (Lundin et al, 2001). This has been explained by Nagy et al (1998). By injecting the spermatozoon into the oocyte, the zona pellucida and cumulus and corona cell barrier is overcome.…”
Section: Discussionmentioning
confidence: 99%
“…First, early cleavage of embryos had to be determined between 23 and 26 h post-injection or 25 and 28 h post-insemination, the time difference being necessary to compensate for the time difference in early development between IVF-and ICSI-derived embryos (Nagy et al, 1994(Nagy et al, , 1998. Second, there had to be at least one normally fertilized (two-pronuclear, 2PN) zygote present.…”
Section: Patientsmentioning
confidence: 99%